First Gaia dynamical model of the Milky Way disc with six phase space coordinates: a test for galaxy dynamics - Nitschai, Maria Selina; Cappellari, Michele; Neumayer, Nadine (Monthly notices of the Royal Astronomical Society, 2020)
We construct the ﬁrst comprehensive dynamical model for the high-quality subset of stellar kinematics of the Milky Way disc, with full 6D phase-space coordinates, provided by the Gaia Data Release 2. We adopt an axisymmetric approximation and use an updated Jeans Anisotropic Modelling (JAM) method, which allows for a generic shape and radial orientation of the velocity ellipsoid, as indicated by the Gaia data, to ﬁt the mean velocities and all three components of the intrinsic velocity dispersion tensor. The Milky Way is the ﬁrst galaxy for which all intrinsic phase space coordinates are available, and the kinematics are superior to the best integral-ﬁeld kinematics of external galaxies. This situation removes the long-standing dynamical degeneracies and makes this the ﬁrst dynamical model highly overconstrained by the kinematics. For these reasons, our ability to ﬁt the data provides a fundamental test for both galaxy dynamics and the mass distribution in the Milky Way disc. We tightly constrain the volume average total density logarithmic slope, in the radial range 3.6-12 kpc, to be αtot = −2.149 ± 0.055 and ﬁnd that the dark halo slope must be signiﬁcantly steeper than αDM = −1 (NFW). The dark halo shape is close to spherical and its density is ρDM(R ) = 0.0115 ± 0.0020 M pc−3 (0.437 ± 0.076 GeV cm−3), in agreement with previous estimates. The circular velocity at the solar position vcirc(R ) = 236.5 ± 3.1 km s−1 (including systematics) and its gently declining radial trends are also consistent with recent determinations.